The proper ways of assessing damages for defective building works - Mohd Suhaimi Mohd Danuri, (Fakulti Undang - Undang, 2006)

(untitled)
Damages are one of the remedies available for a breach of contract. In these circumstances, defective building works constitute a breach of contract by the contractor. This article discusses the proper ways of assessing damages for defective building works. The article reveals three (3) possible measures of damages for defective building works. Whether to award reinstatement cost, diminution in value or loss of amenity/solatium, the essential requirements for the proper assessment of damages are the intention of the owner to remedy the defects and the reasonableness of the intention, and the reasonableness of the remedial works itself. This article suggests how the ‘intention’ and ‘reasonableness’ can be tested by using several questions of facts